Engaging stakeholders to develop a suicide prevention learning module for Louisiana firearm training courses - Claire Houtsma; Jeffrey Powers; Amanda M. Raines; Matthew Bailey; Catherine Barber; Gala True (BMC, 2023)
Abstract Background Firearm suicide is a significant public health problem in the United States of America among the general and veteran populations. Broad-based preventive strategies, including lethal means safety, have been emphasized as a key approach to suicide prevention. Prior research has identified ways to improve the reach and uptake of lethal means safety messages. However, few resources have been created with these lessons in mind. Methods Louisiana firearm owners and instructors were recruited through a larger project, Veteran-Informed Safety Intervention and Outreach Network, as well as a publicly available database of firearm instructors to participate in focus groups to provide feedback on an existing suicide prevention learning module (developed in Utah) for use by firearm instructors. Their feedback was used to adapt the module, which included a brief video and PowerPoint presentation. Firearm owners and instructors were then invited back for another round of focus groups to provide feedback on this adapted learning module. Team-based rapid qualitative analysis was conducted to identify themes across transcripts from these four focus groups. Results Firearm owners and instructors agreed on several key themes, including the importance of messenger relatability and aligning the lethal means safety message with firearm owner values. Feedback suggested these themes were adequately addressed in the adapted learning module and contributed to overall module acceptability. The final theme, present across the original and adapted learning modules (i.e., Utah and Louisiana), was openness to further information and training on firearm suicide prevention. Conclusion Consistent with a public health approach to suicide prevention, the current study used stakeholder engagement to develop a suicide prevention learning module perceived as representative, accurate, and acceptable to Louisiana firearm owners and instructors. These findings can be used to inform firearm suicide prevention efforts in other states.